2001
DOI: 10.1021/jo015734o
|View full text |Cite
|
Sign up to set email alerts
|

Laurenanes:  Fenestranes with a Twist

Abstract: Four isomeric alcohols derived from the diterpene lauren-1-ene (1) have been examined by NMR methods (nuclear Overhauser enhancements, coupling constants, and variable-temperature studies) and by molecular mechanics using the MM3 force field to investigate a conformational twisting of the [5.5.5.7]fenestrane ring system. Results have been correlated with a concurrent study of remote functionalization reactions induced by iodobenzene diacetate/iodine under ultrasonic irradiation. Three of the laurenan-2-ols, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The structure was confirmed by X-ray analysis of the brominated derivative 4, and the angles around the central carbon atom were determined to be 117.98 and 118.98. [24] Laurenene (2) represents the first, and so far only, isolated natural product with an all-carbon fenestrane scaffold. Since its discovery, three total syntheses of laurenene have been completed: those of Crimmins and Gould [25] and Tsunoda et al [26] were published nearly simultaneously in 1987, and the third one by Wender et al [27] one year later.…”
Section: Methodsmentioning
confidence: 99%
“…The structure was confirmed by X-ray analysis of the brominated derivative 4, and the angles around the central carbon atom were determined to be 117.98 and 118.98. [24] Laurenene (2) represents the first, and so far only, isolated natural product with an all-carbon fenestrane scaffold. Since its discovery, three total syntheses of laurenene have been completed: those of Crimmins and Gould [25] and Tsunoda et al [26] were published nearly simultaneously in 1987, and the third one by Wender et al [27] one year later.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous total syntheses of 1 have been achieved recently, [15][16][17] but the genetic and biosynthetic basis for 1 remain unknown. Ap revious hypothesis regarding the biosynthesis of 1 suggested that silphinene (6), an angular triquinane sesquiterpene isolated from various plants and used as an antifeedant, may be an intermediate. [18] It has been proposed that oxidation of 6 at the C15 methyl group yields carboxylic acid 7,w hich can undergo cleavage of the C1-C2 olefin to form dialdehyde intermediate 8.S ubsequent cyclization and oxidation of 8 to al actol (9)a nd d-lactone completes the biosynthesis of 1 (Figure 1b).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…)isoprenoid diphosphates,and is subsequently cyclized by terpene cyclases (TCs) to generate structures that often contain multiply fused ring systems. [5] Among the types of chemical structures observed in cyclized terpenes,avery unique subgroup is those that contain the fenestrane core,a sf ound in the plant diterpene laurenene, [6] which contains four condensed rings and ad istorted tetracoordinated central carbon atom (Figure 1a). [3,4] During the course of this reaction, up to half of the carbon atoms in the linear substrate can undergo changes in C À Cc onnectivity and hybridization to produce quaternary and chiral centres.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes were not made in those cases where the contradiction was caused by the presence of ''anomalous'' chemical shifts in a structure, a so-called ''exotic'' structure. An example of such a structure 8 In structure 7.5 the chemical shift of the quaternary carbon atom that is common to all four cycles is 71.91 ppm, a value which is typical for a carbon neighboring an oxygen atom.…”
Section: Atom Property Correlation Table (Apct)mentioning
confidence: 99%